Effectiveness of Safe Vegetables Production in Thai Binh Province, Vietnam - Van Tuyen Dinh; Quang Hien Truong; Junbiao Zhang (My University, 2018)
Effectiveness of Safe Vegetables Production in Thai Binh Province, Vietnam
Keywords: Rau an toàn; Hiệu quả kinh tế; Tỉnh Thái Bình